2022
DOI: 10.1097/aog.0000000000004695
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Menstrual Cycle Length and Coronavirus Disease 2019 (COVID-19) Vaccination

Abstract: To assess whether coronavirus disease 2019 (COVID-19) vaccination is associated with changes in cycle or menses length in those receiving vaccination as compared with an unvaccinated cohort. METHODS:We analyzed prospectively tracked menstrual cycle data using the application "Natural Cycles." We included U.S. residents aged 18-45 years with normal cycle lengths (24-38 days) for three consecutive cycles before the first vaccine dose followed by vaccine-dose cycles (cycles 4-6) or, if unvaccinated, six cycles ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
252
6
22

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(302 citation statements)
references
References 25 publications
22
252
6
22
Order By: Relevance
“…Although this finding was in line with that from a large and well-designed study carried out in the USA which also detected delays to the period following a dose of the vaccine [13], the delays we found were somewhat larger. We therefore considered the possibility that those participants who had returned their journals were more likely to have noticed any change than those who did not, inflating the postvaccination changes.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Although this finding was in line with that from a large and well-designed study carried out in the USA which also detected delays to the period following a dose of the vaccine [13], the delays we found were somewhat larger. We therefore considered the possibility that those participants who had returned their journals were more likely to have noticed any change than those who did not, inflating the postvaccination changes.…”
Section: Resultssupporting
confidence: 91%
“…Importantly, periods returned to coming at the expected time in the interdose and post-vaccine cycles. These findings are in line with those from a recent study in the USA, which reported increases in cycle length associated with receiving either the second dose of vaccine, or both doses in the same cycle, but again noted that cycles rapidly returned to normal [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our results align with other recent studies which show significant menstrual cycle responsiveness to SARS-CoV-2 vaccination. For example, a Norwegian cohort study found increased reports of heavier periods and longer menstrual bleeding after vaccination which lasted for two to three months ( 86 ), and U.S.-based sample found longer cycle lengths after vaccination but no effect on bleeding duration ( 87 ). The only study published thus far which examined menstrual flow after vaccination had similar findings to ours, specifically that that people using hormonal contraceptives were more likely to experience heavier bleeding after vaccination; however, they did not find an association with diagnosed reproductive conditions although they note their sample size might be too small and underpowered for this analysis ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antivaxxers later highlighted the worries regarding possible vaccine-induced menstrual irregularities, expanding unverified and often manipulative concerns, and promoting fears of vaccine– associated abortions and infertility 3,4 . Recent studies have examined the effects of COVID-19 disease 5 and vaccines 6,7 on menstrual irregularities, suggesting lack of adequate reporting of such irregularities due to women’s reluctance to discuss these matters with their physicians 8 . Yet whether these are anecdotal reports amplified by antivaxxers or a true uncharted association remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%